GENDER OPPORTUNITY GAP AND WAGE DIFFERENTIALS IN THE BANKING SECTOR OF NIGERIA - Onyema, Chiemeka; Princewill, Chikere; Chigbu, Chidimma (African Journal of Social and Behavioural Sciences, 2024)
This study investigated the effects of gender opportunity gap on wage differentials in the banking sector of Nigeria, using Access Bank PLC as a unit of analysis. Specifically, the study investigated the effects of unequal leadership promotion on basic salary differentials between men and women, as well as how unequal work transfer opportunities affect housing allowance payments to men and women. The study employed a survey and descriptive research design. Questionnaires and interview methods were used for data collection. The sample size was 320. Data analysis revealed that there is no significant relationship between unequal leadership promotion and base pay differences for men and women and that there is no significant relationship between unequal work transfer opportunities and housing allowance differentials for men and women. This study bridges a gap in the existing literature by examining specific organizational practices that perpetuate gender-based wage differentials in the Nigerian banking sector. Based on the findings, it was recommended that banks should develop clear and unbiased promotion criteria that are accessible to all employees and regularly review compensation structures to identify and address any discrepancies.